2023
DOI: 10.1177/26345161221147744
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Gastric Cancer and Utility of Endoscopic Screening for Lynch Syndrome Patients

Abstract: Background: Lynch syndrome (LS) is an autosomal dominant hereditary condition associated with a genetic predisposition to several cancers. Prior studies have shown an increased risk of gastric cancer (GC) in LS patients. The aim of this study was to synthesize the evidence for gastric cancer risk across Lynch syndrome-associated mutations and to assess the diagnostic utility of endoscopic screening for gastric cancer in these patients. Methods: A systematic literature review and meta-analysis of LS-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Genetic mutations such as the CDH1 germline mutation or hMLH1 germline mutations make up 2-3% of early-onset gastric cancer cases in North America [64]. A study evaluating the risk of developing gastric cancer in patients with Lynch syndrome found that the cumulative lifetime risk ranges from 3% to 39% across all mutations (MLH1, MSH2, MSH6, PMS2, and EPCAM) [65,110]. Peutz-Jeghers syndrome (PJS) is another hereditary risk factor for early-onset gastric cancer [66].…”
Section: Gastric Cancer: Risk Factors For Early-onset Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic mutations such as the CDH1 germline mutation or hMLH1 germline mutations make up 2-3% of early-onset gastric cancer cases in North America [64]. A study evaluating the risk of developing gastric cancer in patients with Lynch syndrome found that the cumulative lifetime risk ranges from 3% to 39% across all mutations (MLH1, MSH2, MSH6, PMS2, and EPCAM) [65,110]. Peutz-Jeghers syndrome (PJS) is another hereditary risk factor for early-onset gastric cancer [66].…”
Section: Gastric Cancer: Risk Factors For Early-onset Diseasementioning
confidence: 99%
“…A comprehensive review of the literature was performed. [2] Predominantly adenocarcinoma -Cardia -Non-cardia [3,4] Hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC) Predominantly pancreatic ductal adenocarcinoma [5] obesity [40,41] SCC: Oral hygiene, tobacco smoking [42] H. pylori infection, obesity, heavy alcohol use [43][44][45][46][47][48][49][50] HCC: Chronic hepatitis B infection, tobacco smoking [51,52] ICC: Primary sclerosing cholangitis, parasitic infections, hepatolithiasis [53][54][55] Heavy alcohol use, tobacco smoking, diabetes, obesity [56,57] Lower dietary fiber intake, heavy alcohol use, greater red meat consumption, lack of regular nonsteroidal anti-inflammatory drug use, and lower educational level [58,59] Risks for early-onset cancer: genetic, familial Familial Barrett's esophagus [60] Family history, CDH1 germline mutation, Lynch syndrome, juvenile polyposis syndrome, Peutz-Jeghers syndrome [61][62][63][64][65][66][67] HCC: Family history of HCC, family history of hepatitis B infection [68,69] ICC: Congenital disorders of biliary tract [70] Family history of pancreatic ductal adenocarcinoma, multiple germline mutations (BRCA1/2, PALB2, APC ATM, CDKN2A, MLH1, MSH2, MSH6, PMS2, EPCAM STK11, PRSS1) [71][72][73] Lynch syndrome, familial adenomatous polyposis, juvenile polyposis syndrome, Peutz-Je...…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This issue also contains fantastic complementary articles on screening for foregut cancers in Lynch syndrome and surveillance after surgery. 10,11 We are pleased to publish 4 original research articles this month and 1 original review as our journal continues to grow. Dr. Poggi et al share their experience with pre procedure diagnostic testing in a large cohort of bariatric surgery patient.…”
Section: Prefacementioning
confidence: 99%
“…8,9 This issue also contains fantastic complementary articles on screening for foregut cancers in Lynch syndrome and surveillance after surgery. 10,11…”
mentioning
confidence: 99%